The role of interventional sialendoscopy and intraductal steroid therapy in patients with recurrent sine causa sialadenitis: a prospective cross‐sectional study. (6th June 2016) - Capaccio, P.; Torretta, S.; Di Pasquale, D.; Rossi, V.; Pignataro, L.
Abstract : Objectives: To verify the role of interventional sialendoscopy and steroidal ductal irrigation in patients with recurrent sialadenitis. Design: A prospective, cross‐sectional pilot study. Setting: University of Milan. Participants: Fifty‐four patients with sine causa recurrent sialadenitis who underwent interventional sialendoscopy (group A, 36 patients) or interventional sialendoscopy followed by a intraductal steroidal irrigations (group B, 18 patients). Main outcomes measures: The number of episodes of sialadenitis three and 6 months before and after sialendoscopy, and their severity assessed by means of a 0–10 pain visual analogue scale. Results: In the population as a whole, a significant post‐treatment reduction in the number of episodes of 30.7 ± 5.5 after 3 months and 34.6 ± 10.2 after 6 months ( P < 0.001) and a significant reduction in pain visual analogue scale values of 4.7 ± 0.4 after 6 months ( P < 0.001) occurred. There was a statistically significant reduction in both parameters at the same time points in both treatment groups ( P ≥ 0.001), with no significant between‐group difference in pain visual analogue scale values, an albeit non‐significant trend in favour of group B in terms of the number of episodes 3 months after therapy that became significant after 6 months (11.0 ± 9.9 versus 20.5 ± 9.5; P = 0.05). Conclusions: Interventional sialendoscopy is effective for the treatment of recurrent sialadenitis; the addition of intraductal steroidal irrigations seems to increase its value in the medium term. Further studies of larger case series with longer follow‐up are needed to establish the possibly primary role of steroid therapy in blocking inflammation.